2005
DOI: 10.1097/01.mlg.0000161334.67977.5d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukins and Transforming Growth Factor-β in Chronic Rhinosinusitis and Nasal Polyposis

Abstract: IL-6, IL-8, and IL-11 are nonspecific markers of sinus inflammation being transcribed in patients with CRS and patients with CRS/NP. However, patients with CRS/NP demonstrate increased transcription of TGF-beta in response to IL-4 treatment, suggesting an IL-4 mediated mechanism for stromal proliferation in the formation of nasal polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 17 publications
1
34
0
2
Order By: Relevance
“…[13] On the other hand, a variety of other cytokines like IL-6, IL-8, IL-11, IL-16 are nonspecific markers of the inflammation in these patients. [14,15] IL-16 is a highly potent chemotactic and chemoattractant molecule for eosinophils. Lackner et al [15] reported a local increase of IL-16 in nasal polyp tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[13] On the other hand, a variety of other cytokines like IL-6, IL-8, IL-11, IL-16 are nonspecific markers of the inflammation in these patients. [14,15] IL-16 is a highly potent chemotactic and chemoattractant molecule for eosinophils. Lackner et al [15] reported a local increase of IL-16 in nasal polyp tissue.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has been shown to enhance the differentiation of B cells and their consequent production of immunoglobulins. Furthermore, IL-6 has been reported to be a primary inducer of the acute-phase response [21][22][23]. It does not induce cytokine expression; therefore, its main effects are to augment the responses of immune cells like regulatory T cells to other cytokines [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-8 has a wide range of actions on various types of cells, including lymphocytes, monocytes, endothelial cells, and fibroblasts, besides neutrophils [32]. The discovery of these biological functions might suggest that IL-8 is also a marker of sinus inflammation in patients with CRS [21,33]. Beside others Bradley et al showed that IL-8 is a non-specific marker of sinus inflammation being expressed in patients with CRS and patients with CRS/NP [21,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription of TGF-β was found to be 3.2 times greater in patients with chronic rhinosinusitis and nasal polyps than in patients with chronic rhinosinusitis alone. Moreover, patients with chronic rhinosinusitis and nasal polyps demonstrate increased transcription of the TGF-β gene in response to IL-4 treatment, suggesting that a Th2-mediated mechanism may be responsible for stromal proliferation and formation of nasal polyposis [38].…”
Section: Eosinophilsmentioning
confidence: 99%